Nutraceutical Potential of Leafy Vegetables Landraces at Microgreen, Baby, and Adult Stages of Development - Cristina Mallor; Juan Ramón Bertolín; Pablo Paracuellos; Teresa Juan (Foods, 2023)
Nutraceutical compounds present in leafy vegetables have gained substantial attention due to the health benefits they offer beyond their nutritional value. The biosynthesis, composition, and concentration of these compounds vary widely among leafy vegetables and carry the influence of genetic, agronomic, and environmental factors. Recently, micro-vegetables are gaining importance among consumers worldwide and are used in gastronomy at different development stages. Another tendency is the utilization of local genetic resources as an integral component of agricultural biodiversity crucial for sustainable production. The present study identifies the nutraceutical potential of 10 leafy vegetables at the microgreen, baby, and adult development stages using local genetic resources from the Spanish Vegetable Genebank (CITA, Aragón). Specifically, two landraces for each of the following crops were used: chard (Beta vulgaris), spinach (Spinacia oleracea), lettuce (Lactuca sativa), borage (Borago officinalis), and chicory (Cichorium intybus). The results reinforce the value of traditional local genetics and demonstrate the potential of these leafy vegetables as a source of functional compounds (fatty acids, vitamin C, carotenoids, polyphenols, antioxidant activity, and tocopherols). The observed variability depending on the crop and the developmental stage recommends the necessity of having a varied diet, since each leafy vegetable product offers a unique nutritional profile.